Exploring the mechanical impact of fine powder integration from ironwood sawdust and COCO dust particles in epoxy composites - Gurusamy, Mahesh; Soundararajan, Seenivasan; Karuppusamy, Manickaraj; Ramasamy, Karuppasamy (Matéria, 2024)
ABSTRACT Bio-composite materials are gaining momentum as eco-friendly substitutes for synthetic fiber-reinforced composites across various sectors. This study investigates how varying fine powder loads affect the tensile, transverse, and compressive properties of hybrid composites comprising Malabar Ironwood sawdust and COCO dust particles. A hybrid composite formulation was devised using a 1:1 ratio of sawdust and COCO dust particles as fillers. Different levels of reinforcement, ranging from 20% to 60%, were examined. ASTM testing was performed on the produced composites, revealing a notable influence of filler reinforcement on their mechanical characteristics. The elongation at fracture increased until 40% filler loading before declining, whereas tensile strength, transverse rupture strength, transverse modulus, and compressive strength consistently improved up to 50% filler loading. These results underscore the potential of composites integrating Malabar Ironwood, COCO dust, and epoxy for lightweight applications, thereby catering to diverse industries seeking sustainable alternatives to traditional materials. Ultimately, such initiatives contribute to solid waste management efforts, offering sustainable alternatives to conventional materials in diverse industries.